Cystic tumors of the pancreas - Campos Pierri, Néstor; Veroli Salvia, Antonio; Mascari Burutaran, José L; Campos Tasende, Néstor A (Cirugía del Uruguay, 2002)
Case material consists of five patients, four of them coresponding to cystic tumors of pancreas and one to a pseudocyst which, as literature tells us, is often dificult to differentiate rom the former. There is a description of main clinical and image aspects and the conduct applied thereto